Literature Review: The Role of Early Childhood Education Institutions in Early Detection of Attention Deficit Hyperactivity Disorder (ADHD) - Kabul Suprayitno; Evi Agustin (HADHANATUNA: Journal of Early Childhood Education, 2025)
Attention Deficit Hyperactivity Disorder (ADHD) is a developmental behavioral disorder characterized by difficulties in maintaining attention, hyperactivity, and impulsivity. This condition can appear as early as the preschool years and may affect children’s academic, social, and emotional development. Early Childhood Education (PAUD) institutions serve as a strategic environment for consistent observation of children’s behavior through learning and play activities. This study aims to describe the role of PAUD institutions in the early detection of ADHD. The research applies a narrative review method by analyzing relevant scholarly literature from Google Scholar, PubMed, Elsevier, and other reputable journals. The findings reveal that PAUD institutions play a vital role in identifying early signs of ADHD through daily behavioral observations. Teachers act as the primary observers who can recognize symptoms of inattention, hyperactivity, and impulsivity. Moreover, enhancing teachers’ competencies and fostering collaboration among educational institutions, parents, and professionals are essential to ensure effective early detection. Thus, PAUD institutions are not only responsible for providing early education but also act as the frontline in promoting children’s comprehensive development and mental well-being through a structured early detection system.